Preverbal visual photo screening Project implementation in Portugal - Carneiro,Inês (2018)
Abstract Purpose: To present the design and implementation of an amblyopia risk factors screening project, in a large based Portuguese population. Methods: Two referral centers have been enrolled to assess all children aged 2 under their direct referral area. The photoscreener used was PlusOptix ® A09. At this age, the cut-off defined for referral was: ≥1 Diopter (D) of anisometropia, ≥1.5D of astigmatism, ≥2D of myopia and ≥1.5D of hyperopia. The results were reported to a reading platform that allowed the ophthalmologist to see all exams, and provide timely appointment with a complete ophthalmologic assessment for those who needed. Results: A total of 2867 photo screens were made to the population eligible to both referral centers, which comprises a coverage rate of 55%. Out of 2611 children under one of the referral area, 53% (n=1395) adhered to the screening. Within these children, 17.5% (n=245) were referred and 15.3 % (n=214) appointments were performed. The comparison of refraction between PlusOptix ® and cycloplegic refraction showed a strong correlation regarding the sphere and cylinder values. From the 214 children observed in consultation, glasses were prescribed in 25.7% (n=55), corresponding to 3.9% of all screened children under one of the referral area. This screening method showed a positive predictive value of 58.4%. Conclusion: This screening program may be highly relevant to eradicate untreated amblyopia from our population. The results may lead to the implementation of this project to the whole country.